2016
DOI: 10.1016/j.ipej.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between IEGM-based approach and echocardiography in AV/PV and VV delay optimization in CRT-D recipients (Quicksept study)

Abstract: BackgroundAtrioVentricular (AV) and InterVentricular (VV) delay optimization can improve ventricular function in Cardiac Resynchronization Therapy (CRT) and is usually performed by means of echocardiography. St Jude Medical has developed an automated algorhythm which calculates the optimal AV and VV delays (QuickOpt™) based on Intracardiac ElectroGrams, (IEGM), within 2 min. So far, the efficacy of the algorhythm has been tested acutely with standard lead position at right ventricular (RV) apex. Aim of this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The Quicksept study showed that aortic velocity time integral (aVTI) values at the optimized AV and VV intervals as determined by echocardiography and by the QuickOpt algorithm were quite well correlated and that this correlation was maintained in long-term follow-up [ 5 , 59 ]. AV and VV delay optimization data were collected in 13 centres using both echocardiographic and QuickOpt guidance in CRT-D implanted patients provided with this algorithm [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Quicksept study showed that aortic velocity time integral (aVTI) values at the optimized AV and VV intervals as determined by echocardiography and by the QuickOpt algorithm were quite well correlated and that this correlation was maintained in long-term follow-up [ 5 , 59 ]. AV and VV delay optimization data were collected in 13 centres using both echocardiographic and QuickOpt guidance in CRT-D implanted patients provided with this algorithm [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Speckle tracking echocardiography (STE) has been reported as a useful imaging method to detect CRT responders [ 3 , 4 ]. Atrioventricular (AV) and interventricular (VV) delay optimization can augment ventricular function in CRT and is usually performed utilizing echocardiography [ 5 ]. The conflicting evidence can be attributed to a combination of factors including poor precision, lack of experience, short follow-up time, late responders, or failure to distinguish non-responders.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, two MPP configurations guided by QuickOpt™ were shown to provide the most improvement with PEP compared to a fixed VV delay of 5 ms or 15 ms. However, as with other device‐based CRT optimization tools, QuickOpt™ has not been shown to be superior to echo optimization methods or improve hard clinical outcomes …”
Section: Discussionmentioning
confidence: 99%
“…However, as with other device-based CRT optimization tools, QuickOpt TM has not been shown to be superior to echo optimization methods or improve hard clinical outcomes. 13,17,18…”
Section: Multipoint Pacing Versus Conventional Crt In Arterial Tonomementioning
confidence: 99%
“…Our study is the fi rst to show that manual IEGM can be used for VV optimization after CRT implantation, even for devices that do not have automated IEGM system. Previous studies have shown that IEGM is an accurate alternative to time-consuming echocardiography techniques for VV optimization 14,18,[23][24][25] . St Jude's CRT devices have automated IEGM systems, which can accurately calculate AV and VV delay in one minute.…”
Section: Discussionmentioning
confidence: 99%